2015
DOI: 10.3201/eid2106.141103
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella entericaSerotype Enteritidis in French Polynesia, South Pacific, 2008–2013

Abstract: Outbreaks of Salmonella enterica serotype Enteritidis infections associated with eggs occurred in French Polynesia during 2008–2013. Molecular analysis of isolates by using clustered regularly interspaced short palindromic repeat polymorphisms and multilocus variable-number tandem-repeat analysis was performed. This subtyping made defining the epidemic strain, finding the source, and decontaminating affected poultry flocks possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Seven studies about resistance patterns in Salmonella spp. in PICTs were identified (Table 3) [18,21,40,41,42,43,44]. The earliest study (1987) about non-typhoidal Salmonella (NTS) was from PNG’s Eastern Highlands Province [18], where 58% (22/38) of isolates were resistant to chloramphenicol, 37% (14/38) to kanamycin, 53% (20/38) to ampicillin and 6% (2/38) to tetracycline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies about resistance patterns in Salmonella spp. in PICTs were identified (Table 3) [18,21,40,41,42,43,44]. The earliest study (1987) about non-typhoidal Salmonella (NTS) was from PNG’s Eastern Highlands Province [18], where 58% (22/38) of isolates were resistant to chloramphenicol, 37% (14/38) to kanamycin, 53% (20/38) to ampicillin and 6% (2/38) to tetracycline.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, although S. typhi has been reported increasingly in Fiji since 2005, ABR was uncommon [44]. Ninety-six S. enteritidis isolates cultured during an outbreak in French Polynesia (2008 to 2013) were the subject of a laboratory study [43] and resistance to amoxicillin was found in only three isolates. A surveillance study conducted in 2011 in the PNG Highlands following a cholera outbreak found 2.3% of isolates to be S. typhi (5/216) [41]: all were resistant to ampicillin, tetracycline, co-trimoxazole and chloramphenicol and one isolate was also resistant to nalidixic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Among the microbial pathogens, bacteria are one of the main causes of diarrhea. From 2008 to 2013, several outbreaks of Salmonella enterica serotype enteritidis infections were reported and contaminated about a hundred of persons (Le Hello et al, 2015). In 2020, 40 cases of acute gastro-enteritis were recorded, among which 35 were due to Salmonella species contamination (BSS, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Simon Le Hello and coworkers in 2013 reported that CRISPR sequences are very applicable targets for subtyping of Salmonella enteritidis isolates. They concluded that since CRISPR spacer content can be easily obtained from short-read DNA sequences, it could be used to identify particular Salmonella and probably other bacterial pathogens [ 89 , 90 ]. Also, Touchon et al .…”
Section: Occurrence and Epidemiological Applications Of Crispr Systemmentioning
confidence: 99%